2010
DOI: 10.1148/radiol.10092279
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Ovarian Cancer: Use of Contrast-enhanced CT and PET/CT to Accurately Localize Tumor Recurrence and to Predict Patients’ Survival

Abstract: Purpose:To compare accuracy and interobserver variability in the detection and localization of recurrent ovarian cancer with contrast material-enhanced (CE) computed tomography (CT) and positron emission tomography (PET)/CT and determine whether imaging fi ndings can be used to predict survival. Materials and Methods:Waiving informed consent, the institutional review board approved this HIPAA-compliant, retrospective study of 35 women (median age, 54.4 years) with histopathologically proven recurrent ovarian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 31 publications
1
33
0
2
Order By: Relevance
“…Avril et al (22) demonstrated that OC patients responding to chemotherapy showed a longer median OS than non-responders. Only three studies evaluated the prognostic role of PET (7) and PET/CT (23,24) in patients with OC after primary treatment. The results by Kurosaki et al (7) are similar to the present report, showing that the serum CA125 level significantly correlated with the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Avril et al (22) demonstrated that OC patients responding to chemotherapy showed a longer median OS than non-responders. Only three studies evaluated the prognostic role of PET (7) and PET/CT (23,24) in patients with OC after primary treatment. The results by Kurosaki et al (7) are similar to the present report, showing that the serum CA125 level significantly correlated with the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the main limitation of CE CT is the reduced sensitivity (~50%) for the detection of peritoneal implants <10 mm (28), or for the differentiation of these from fibrous residual after treatment. However, there are no reliable data which favor PET/CT rather than CE CT and vice versa (29).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 10−30 mL saline flush is done after IV FDG injection [26,28]. In order to allow even biodistribution and sufficient cellular uptake of FDG, the patients should not immediately undergo PET/CT after the injection of FDG, but they should rather wait for at least 40−60 min before the scanning [18,26,27,29,30 ]. If it is not possible to place a venous access, FDG can also be administered orally in liquid form with water [16,18].…”
Section: Administration Of Fdgmentioning
confidence: 99%
“…Prior to abdominal PET/CT imaging, diluted iodinated CM or barium sulfate as positive contrast agents are administered orally for the opacification of gastrointestinal system [5,27,29,30,33,34]. Water or water-based negative contrast agents were also recommended as intraluminal CMs since they were reported to help increase the quality of the images with decreased artifacts [35].…”
Section: Administration Of Radiologic Contrast Materialsmentioning
confidence: 99%